Medication error in Outpatient Pharmacy at Hospital Tuanku Ja'afar, Seremban - Khairul Azma, Nurul Shahidah (2011)
Medication error any incorrect or wrongful administration of a medication, such as a mistake in dosage or route of administration, failure to prescribe or administer the correct drug or formulation for a particular disease or condition, use of outdated drugs, failure to observe the correct time for administration of the drug, or lack of awareness of adverse effects of certain drug combinations. Causes of medication error may include difficulty in reading handwritten orders, confusion about different drugs with similar names, and lack of information about a patient's drug allergies or sensitivities. When the nurse is in doubt, administration of a drug should be delayed until specifically authorized by a physician. Objective of this research to determine the major source of medication error and to give some idea how to prevent of medication error. The analization of the data was done obtained by performing surveillance on 80 patients at outpatients in HOSPITAL TUANKU JA'AFAR SEREMBAN (external survey).For internal survey done in outpatient pharmacy area, I placed survey form at the screening area to attach on the prescription so that staff can done the surveys. From the surveys the highest patient have done medication error are among the 60-65 years old patients and female patients and the most high risk area to make medication error at filling area. The conclusion of the surveys are patients have get medication error because of not understand instruction given by pharmacist